2014
DOI: 10.1016/j.radonc.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Role of endorectal MR imaging and MR spectroscopic imaging in defining treatable intraprostatic tumor foci in prostate cancer: Quantitative analysis of imaging contour compared to whole-mount histopathology

Abstract: Purpose To investigate the role of endorectal MR imaging and MR spectroscopic imaging in defining the contour of treatable intraprostatic tumor foci in prostate cancer, since targeted therapy requires accurate target volume definition. Materials and Methods We retrospectively identified 20 patients with prostate cancer who underwent endorectal MR imaging and MR spectroscopic imaging prior to radical prostatectomy and subsequent creation of detailed histopathological tumor maps from whole-mount step sections.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 22 publications
0
26
1
2
Order By: Relevance
“…22 MR sequences was not studied by these authors. Anwar et al compared delineations by two observers on T2w imaging and MR spectroscopy with delineations on histology and found these to differ by a median distance of 1.4 mm [14].…”
Section: Introductionmentioning
confidence: 99%
“…22 MR sequences was not studied by these authors. Anwar et al compared delineations by two observers on T2w imaging and MR spectroscopy with delineations on histology and found these to differ by a median distance of 1.4 mm [14].…”
Section: Introductionmentioning
confidence: 99%
“…The average diameter of target lesions in low-and intermediate-risk patients was 1.4 and 1.5 cm, corresponding to treatment volumes of 1.4 and 1.8 cm 3 . Recent work comparing imaging-defined lesions to pathologic specimens demonstrates that a 5 mm margin on imaging-defined lesions covers 95% of the tumor volume that is missed on the imaging-defined capsular border alone (10). Adding a 5 mm margin to the MRI-defined lesions results in mean treatment volumes of 3.5 and 4.3 cm 3 for lowand intermediate-risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of patients undergoing endorectal multiparametric MRI prior to radical prostatectomy (n = 88) demonstrated that all T2-weighted tumor targets were correctly identified dominant tumor foci when associated with at least 0.54 cm 3 of concordant spectroscopic imaging abnormality [58]. A subsequent study (n = 20) employing this definition of target tumor showed that all 9 tumor foci independently identified by both readers were correctly identified dominant tumor sites, but 5 lesions identified by only one reader were all false positives [67]. This suggests that identification of treatable tumor foci prior to MR-guided HIFU for prostate cancer should require both multiparametric and independent multi-reader confirmation.…”
Section: Patient Selection and Target Definitionmentioning
confidence: 94%
“…A study utilizing multiparametric MRI data and quantitative analysis of imaging contour compared to whole-mount histopathology adequate tumor coverage is achieved by expanding the treatment contour at the non-capsular margin by 5 mm, with no expansion required at the capsular margin [67].…”
Section: Patient Selection and Target Definitionmentioning
confidence: 99%